Discretionary Policy, Multiple Equilibria, and Monetary Instruments - Andreas Schabert (Tinbergen Institute, 2005)
This paper examines monetary policy implementation in a sticky price model. The central bank's plan under discretionary optimization is entirely forward-looking and exhibits multiple equilibrium solutions if transactions frictions are not negligibly small. The central bank can then implement stable history dependent equilibrium sequences that are consistent with its plan by inertial interest rate adjustments or by money injections. These equilibria are associated with lower welfare losses than a forward-looking solution implemented by interest rate adjustments. The welfare gain from a history dependent implementation is found to rise with the strength of transactions frictions and the degree of price flexibility. It is further shown that the central bank's plan can uniquely be implemented in a history dependent way by money injections, whereas inertial interest rate adjustments cannot avoid equilibrium multiplicity.
Keywords: E52; E51; E32; 330; Monetary policy implementation; optimal discretionary policy; history dependence; equilibrium indeterminacy; money growth policy; Geldpolitik; Wohlfahrtsanalyse; Geldmengensteuerung; Theorie